Control error dynamic modification as an efficient tool for reduction of effects introduced by actuator constraints - Janiszowski, Krzysztof B. (Zielona Góra: Uniwersytet Zielonogórski)
A modification of digital controller algorithms, based on the introduction of a virtual reference value, which never exceeds active constraints in the actuator output is presented and investigated for some algorithms used in single-loop control systems. This idea, derived from virtual modification of a control error, can be used in digital control systems subjected to both magnitude and rate constraints. The modification is introduced in the form of on-line adaptation to the control task. Hence the design of optimal (in a specified sense) digital controller parameters can be separated from actuator constraints.
Keywords: actuator constraints; digital dead-beat control; PID control; rate constraints; state space control; saturations at control; wind-up